Proceedings of the Second International Conference on Internet of Things, Data and Cloud Computing 2017
DOI: 10.1145/3018896.3025130
|View full text |Cite
|
Sign up to set email alerts
|

Cloud computing service discovery framework for IaaS and PaaS models

Abstract: Cloud service discovery is a new challenge which requires a dedicated framework in order to approach it. Over the past few years, several methods and frameworks have been developed for cloud service discovery but they are mostly designed for all cloud computing models in general which are not optimal. The three cloud computing models are Infrastructure as a Service (IaaS), Platform as a Service (PaaS) and Software as a Service (SaaS), each computing model has its own set of resources. Having one single discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Most of the previous works have focused on the efficient discovery results, without taking into account the problems and drawbacks of the mobile environment and wireless devices [8,[10][11][12][13][14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous works have focused on the efficient discovery results, without taking into account the problems and drawbacks of the mobile environment and wireless devices [8,[10][11][12][13][14].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it allowed to add or remove cloud service information without having to change the search functions that were written for the query engine. The results showed that this syntax-based framework is good enough for discovering IaaS and PaaS cloud services [13].…”
Section: Introductionmentioning
confidence: 96%